Skin Delivery of Kojic Acid-Loaded Nanotechnology-Based Drug Delivery Systems for the Treatment of Skin Aging - Goncalez, M. L. [UNESP]; Correa, Marcos Antonio [UNESP]; Chorilli, Marlus [UNESP] (Hindawi Publishing Corporation, 2013)
The aging process causes a number of changes in the skin, including oxidative stress and dyschromia. The kojic acid (KA) is iron chelator employed in treatment of skin aging, and inhibits tyrosinase, promotes depigmentation. Nanotechnology-based drug delivery systems, such as liquid crystalline systems (LCSs), can modulate drug permeation through the skin and improve the drug activity. This study is aimed at structurally developing and characterizing a kojic acid-loaded LCS, consists of water (W), cetostearyl isononanoate (oil-O) and PPG-5-CETETH-20 (surfactant-S) and evaluating its in vitro skin permeation and retention. Three regions of the diagram were selected for characterization: A (35% O, 50% S, 15% W), B (30% O, 50% S, 20% W) and C (20% O, 50% S, 30% W), to which 2% KA was added. The formulations were subjected to polarized light microscopy, which indicated the presence of a hexagonal mesophase. Texture and bioadhesion assay showed that formulation B is suitable for topical application. According to the results from the in vitro permeation and retention of KA, the formulations developed can modulate the permeation of KA in the skin. The in vitro cytotoxic assays showed that KA-unloaded LCS and KA-loaded LCS didn't present cytotoxicity. PPG-5-CETETH-20-based systems may be a promising platform for KA skin delivery.